Nuclear–Electron Correlation Effects and Their Photoelectron Imprint in Molecular XUV Ionisation - Ziems, Karl Michael; Bruhnke, Jakob; Engel, Volker; Gräfe, Stefanie (Frontiers in Chemistry, 2022)
Ionisation of molecules by attosecond XUV pulses is accompanied by complex correlated dynamics, such as the creation of coherent electron wavepackets in the parent ion, their interplay with nuclear wavepackets, and a correlated photoelectron moving in a multi-centered potential. Additionally, these processes are influenced by the dynamics prior and during the ionisation. To fully understand and subsequently control the ionisation process on different time scales, a profound understanding of electron and nuclear correlation is needed. Here, we investigate the effect of nuclear-electron correlation in a correlated two-electron, one-nucleus quantum model system. Solving the time-dependent Schrödinger equation allows to monitor the correlation impact pre, during and post XUV ionisation. We show how an initial nuclear wave packet displaced from equilibrium influences the post-ionisation dynamics by means of momentum conservation between the target and parent ion, whilst the attosecond electron population remains largely unaffected. We calculate time-resolved photoelectron spectra and their asymmetries and demonstrate how the coupled electron-nuclear dynamics are imprinted on top of electron-electron correlation on the photoelectron properties. Finally, our findings give guidelines towards when correlation resulting effects have to be incorporated and in which instances the exact correlation treatment can be neglected.